Letter - Woolwich and District Trades and Labour Club, 5 May 1926 (page 1) (Woolwich)
1926-05-05 "Letter - Woolwich and District Trades and Labour Club, 5 May 1926 (page 1)" [g0259001.jpg], 5 May 1926 Local Organisation